Increased Atherosclerotic Lesions in LDL Receptor Deficient Mice With Hematopoietic Nuclear Receptor Rev‐erbα Knock‐ Down. Issue 4 (20th August 2013) - Ma, Hongling; Zhong, Wenbin; Jiang, Yingliang; Fontaine, Coralie; Li, Shiqian; Fu, Jiangnan; Olkkonen, Vesa M.; Staels, Bart; Yan, Daoguang
Abstract : Background: Nuclear receptor Rev‐erbα plays important roles in circadian clock timing, lipid metabolism, adipogenesis, and vascular inflammation. However, the role of Rev‐erbα in atherosclerotic lesion development has not been assessed in vivo. Methods and Results: The nuclear receptor Rev‐erbα was knocked down in mouse haematopoietic cells by means of shRNA‐lentiviral transduction, followed by bone marrow transplantation into LDL receptor knockout mice. The Rev‐erbα protein in peripheral macrophage was reduced by 70% as compared to control mice injected with nontargeting shRNA lentivirus‐transduced bone marrow. A significant increase in atherosclerotic lesions was observed around the aorta valves as well as upon en face aorta analysis of Rev‐erbα knock‐down bone marrow recipients ( P <0.01) as compared to the control mice, while plasma cholesterol, phospholipid, and triacylglycerol levels were not affected. Overexpression of Rev‐erbα in bone marrow mononuclear cells decreased inflammatory M1 while increasing M2 macrophage markers, while Rev‐erbα knock down increased the macrophage inflammatory phenotype in vitro and in vivo. Furthermore, treatment of differentiating macrophages with the Rev‐erbα ligand heme promoted expression of antiinflammatory M2 markers. Conclusions: These observations identify hematopoietic cell Rev‐erbα as a new modulator of atherogenesis in mice.